Experimental research on self-preservation effect of methane hydrate in porous sediments. (15th June 2020) - Xie, Yan; Zheng, Tao; Zhong, Jin-Rong; Zhu, Yu-Jie; Wang, Yun-Fei; Zhang, Yu; Li, Rui; Yuan, Qing; Sun, Chang-Yu; Chen, Guang-Jin
Highlights: The presence of porous sediments does not influence the self-preservation region. CH4 hydrate dissociation rate is inversely to initial water content and sand size. An enhanced self-preservation effect was found in bentonite and kaolin systems. The interaction of hydrogen bonds between bentonite and hydrate may cause abnormal. The interaction of Na + ions alters force field distribution between CH4 and water. Abstract: The self-preservation is considered as an advantageous property for natural gas hydrate transportation and storage. However, it may also bring serious troubles for well drilling and hydrate exploitation. In this work, various factors affecting the self-preservation effect of CH4 hydrate were investigated by using HP μ-DSC. The results indicate the presence of porous sediments does not influence the anomalous self-preservation region of CH4 hydrate. The CH4 hydrate dissociation rate increases with the decreased initial water content and quartz sand particle size as a whole. However, the self-preservation could be still found in a very low initial water content (10 vol%) and small-particle sediments (25–38 μm) condition. On the other hand, an enhanced self-preservation effect and excessive pressure phenomenon were unexpectedly found in bentonite and kaolin. The hydrate can still maintain high metastability with hardly any decomposition after the pressure was released to atmospheric pressure. In situ Raman and CCD camera were used for the further study of the mechanism. We speculate the interaction of hydrogen bonds between bentonite and hydrate might be the main reason for this abnormal phenomenon. The knowledge gained in this work is significant for the comprehension of CH4 hydrate dissociation in porous sediments below ice point, and provides a better understanding of the self-preservation mechanism.